Role of Fractional Exhaled Nitric Oxide for Monitoring Bronchial Asthma - Lamichhane, Buddhi Sagar; Dhungana, Ashesh; Shrestha, Prajowl; Raj Thapa, Kamal; Shrestha, Deepa Kumari (Journal of Nepal Health Research Council, 2024)
Background: Monitoring during treatment of asthma is usually done by various clinical tools, spirometry, sputum eosinophils and fractional exhaled nitric oxide. Fractional exhaled nitric oxide is a simple and noninvasive tool and has a good agreement with asthma control test score. This study aims to correlate fractional exhaled nitric oxide with asthma control test score. Methods: This cross-sectional study was conducted at National Academy of Medical Sciences, Bir hospital, Chest unit, Department of Medicine, over a duration of six months. Patients aged more than 18 years with bronchial asthma diagnosed at least three months prior were included into the study. Those with recent severe exacerbations, known other chronic respiratory disease and smokers were excluded. Asthma control test score was obtained at baseline. All included patients underwent fractional exhaled nitric oxide measurement followed by measurement of Forced vital capacity(FVC) Forced expiratory volume in one second (FEV1) and FEV1/FVC ratio. Results: Forty patients with a mean age of 40.5±11.1 years were included in the study. Majority were females (65%) and the median duration of symptoms was 24 months (Interquartile range= 18-60). Mean fractional exhaled nitric oxide level was 27.8 (±16.0) parts per billion (ppb) and asthma control test score was 19.3 (±4.7). Mean fractional exhaled nitric oxide levels were significantly different across different severity (well controlled, partially controlled and poorly controlled) of asthma (p=0.013). The mean fractional exhaled nitric oxide values and total asthma control test score shows statistically significant negative correlation (Pearson correlation coefficient (r) = -0.462, p=0.003). Asthma control test and FeNO values guided the change of inhaled steroid dose in 17 of the 40 patients. Conclusion: Fractional exhaled nitric oxide can be used when available, along with asthma control test for monitoring control and adjusting the inhaled steroid dose in asthma. Keywords: Asthma control test (ACT); bronchial asthma; Fractional exhaled nitric oxide (FeNO).